Influence of Mg Doping on ZnO Nanoparticles for Enhanced Photocatalytic Evaluation and Antibacterial Analysis - Pradeev Raj, K.; Sadaiyandi, Karuppasamy; Kennedy, A.; Sagadevan, Suresh; Chowdhury, Zaira Zaman; Johan, Mohd Rafie; Aziz, Fauziah Abdul; Rafique, Rahman Faizur; Thamiz Selvi, Rajamanickam; Rathina Bala, R. (SpringerOpen, 2018)
In this research, a facile co-precipitation method was used to synthesize pure and Mg-doped ZnO nanoparticles (NPs). The structure, morphology, chemical composition, and optical and antibacterial activity of the synthesized nanoparticles (NPs) were studied with respect to pure and Mg-doped ZnO concentrations (0–7.5 molar (M) %). X-ray diffraction pattern confirmed the presence of crystalline, hexagonal wurtzite phase of ZnO. Scanning electron microscope (SEM) images revealed that pure and Mg-doped ZnO NPs were in the nanoscale regime with hexagonal crystalline morphology around 30–110 nm. Optical characterization of the sample revealed that the band gap energy (Eg) decreased from 3.36 to 3.04 eV with an increase in Mg2+ doping concentration. Optical absorption spectrum of ZnO redshifted as the Mg concentration varied from 2.5 to 7.5 M. Photoluminescence (PL) spectra showed UV emission peak around 400 nm. Enhanced visible emission between 430 and 600 nm with Mg2+ doping indicated the defect density in ZnO by occupying Zn2+ vacancies with Mg2+ ions. Photocatalytic studies revealed that 7.5% Mg-doped ZnO NPs exhibited maximum degradation (78%) for Rhodamine B (RhB) dye under UV-Vis irradiation. Antibacterial studies were conducted using Gram-positive and Gram-negative bacteria. The results demonstrated that doping with Mg ions inside the ZnO matrix had enhanced the antibacterial activity against all types of bacteria and its performance was improved with successive increment in Mg ion concentration inside ZnO NPs.